ANALISIS MINAT BELAJAR PENJAS TERHADAP KEMAMPUAN BERMAIN SEPAKBOLA PADA SISWA PUTERA SMA NEGERI 1 LAMURU KABUPATEN BONE - Andi Ogo Darminto (Jurnal Genta Mulia, 2017)
The aim of the research is to find out: "To analyze the influencing factors interest in learning physical education on the ability to play football among boys' students at SMA Negeri 1 Lamuru Bone Regency”. The research problem is "What factors influence interest in learning Physical education on the ability to play football among students at SMA Negeri 1 Lamuru, Bone Regency?” The population of this study were all male students of SMA Negeri 1 Lamuru, Bone Regency. Taking The sample in this study used a simple random sampling technique, namely taking samples randomly randomly using a lottery technique, totaling 40 male students of SMA Negeri 1 Lamuru, Bone Regency as research sample. The research variables are interest in learning physical education and ability to play football. Method Data collection uses questionnaire techniques, measurement tests and documentation. Data analyzed using descriptive percentage analysis and correlation analysis. The research results show that interest studying physical education for boys' students at SMA Negeri 1 Lamuru, Bone Regency, based on an interest indicator of 62.5% of respondents who have an interest in learning physical education are in the high category, the attention indicator is 70% in the high category, and the needs indicator is 62.5% in the high category. The background students' interest in taking physical education lessons is the desire to be able to excel and have physical fitness and be the best in physical education lessons.